Public and private sphere in transnational space: gender, policy and social action between Europe and Latin America: genere, politica e azione sociale tra Europa e America Latina (Italiano, English, Español) - Chiappelli, Tiziana; Mancaniello, Maria Rita; Aguilar Edwards, Andrea (Comparative Cultural Studies: European and Latin American Perspectives, 2016)
--